Protocol for mechanochemistry-guided assembly strategy for enzyme encapsulation using covalent organic frameworks - Rui Gao; Xiaoxue Kou; Rongwei He; Yujiang Shen; Lihong Guo; Hao Wang; Siming Huang; Guosheng Chen; Gangfeng Ouyang (STAR Protocols, 2023)
Summary: Enzyme immobilization into porous frameworks is an emerging strategy for enhancing the stability of dynamic conformation and prolonging the lifespan of enzymes. Here, we present a protocol for a de novo mechanochemistry-guided assembly strategy for enzyme encapsulation using covalent organic frameworks. We describe steps for mechanochemical synthesis, enzyme loading measurements, and material characterizations. We then detail evaluations of biocatalytic activity and recyclability.For complete details on the use and execution of this protocol, please refer to Gao et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.